2021
DOI: 10.1097/ajp.0000000000000968
|View full text |Cite
|
Sign up to set email alerts
|

Clinimetric Properties of Self-reported Disability Scales for Whiplash

Abstract: Objectives: A core outcomes set (COS) for whiplash-associated disorders (WADs) has been proposed to improve consistency of outcome reporting in clinical trials. Patient-reported disability was one outcome of interest within this COS. The aim of this review was to identify the most suitable tools for measuring self-reported disability in WAD based on clinimetric performance.Methods: Database searches took place in 2 stages. The first identified outcome measures used to assess self-reported disability in WAD, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Content validity of the NDI has been examined in people with nontraumatic neck pain and found to be poor, 1 although these findings may not necessarily extrapolate to WAD. 14 Moderate- to high-quality evidence for sufficient psychometric performance of both the NDI and WDQ with respect to structural validity, internal consistency, reliability (ICC 0.84-0.98), construct validity (74%-82% of hypotheses accepted), and responsiveness (majority of correlations in accordance with hypotheses) was found. 14 Because of the very low–quality evidence for the content validity of both instruments, the strength of recommendations was downgraded from level A to level B, meaning that further evaluation of both is necessary, and it was concluded that neither could be recommended over the other.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Content validity of the NDI has been examined in people with nontraumatic neck pain and found to be poor, 1 although these findings may not necessarily extrapolate to WAD. 14 Moderate- to high-quality evidence for sufficient psychometric performance of both the NDI and WDQ with respect to structural validity, internal consistency, reliability (ICC 0.84-0.98), construct validity (74%-82% of hypotheses accepted), and responsiveness (majority of correlations in accordance with hypotheses) was found. 14 Because of the very low–quality evidence for the content validity of both instruments, the strength of recommendations was downgraded from level A to level B, meaning that further evaluation of both is necessary, and it was concluded that neither could be recommended over the other.…”
Section: Resultsmentioning
confidence: 92%
“…The results of the systematic reviews of core measurement instruments for Physical Functioning, Perceived Recovery, Psychological Functioning, and Pain have been published elsewhere. 4,14,20,28…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations